Short-term and 1-year outcomes after MitraClip therapy in functional versus degenerative mitral regurgitation patients: a systematic review and meta-analysis - Liu, Xiao-Hang; Shi, Jia-Yu; Feng, Xiao-Jin; Feng, Dong-Cai; Wang, Lin; Pang, Hai-Yu; Xie, Hong-Zhi; Wang, Fang-Fei; Hsu, Jeffrey; Jia, Fu-Wei; Chen, Wei (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: Differences in short-term and 1-year outcomes of percutaneous edge-to-edge mitral repair between patients with functional and degenerative mitral regurgitation (MR) remain unclear. We performed a systematic review and meta-analysis to investigate the safety and efficacy of MitraClip (MC) in patients with different MR etiologies. Methods: This study systematically searched three common databases for studies on MC therapy until November 2017. The studies meeting the standard inclusion criteria were included. The data at baseline, short-term and 1-year clinical and echocardiographic outcomes were obtained and analyzed. All data were checked by another reviewer. Results: Thirteen studies totalling 2,351 patients investigating the short-term and 1-year outcomes of MC in patients with functional MR (FMR) versus degenerative MR (DMR) were included for further analysis. FMR patients presented a higher risk profile at baseline. There was no difference in short-term outcomes between DMR and FMR for post-procedural MR grade 0–2 (76.8% vs. 77.1%; P=0.428), mean trans-mitral gradient (3.92 vs. 3.50 mmHg; P=0.098), 30-day mortality rate (0.05% vs. 0.03%; P=0.118) and 30-day NYHA I–II (85.3% vs. 78.7%; P=0.211). FMR patients had a higher rate of acute procedural success compared to the DMR patient group (91.2% vs. 95.2%; P=0.016). A greater portion of DMR patients implanted two or more MCs than the FMR patients (41.4% vs. 35.7%; P=0.043). For the 1-year outcomes, no difference was found in the mortality rate (13.0% vs. 15.2%; P=0.268) and proportion of patients with post-procedural MR grades 0–2 (75.0% vs. 80.7%; P=0.106). Conclusions: Despite a higher risk profile in FMR patients, the short-term and 1-year outcomes were not significantly different. We conclude that MC therapy is similar between FMR and DMR patients until 1-year follow-up. Large randomized trials are warranted to fully and further assess the clinical impact of the procedure in these two MR etiologies over a longer period of time.